Desenvolvimento de uma plataforma para ensino de conceitos básicos de lógica de programação Utilizando arduino e android - NEGRÃO, Victor Luiz Santos (2025)
This paper presents the development of a platform dedicated to programming logic teaching for children using Arduino and Android, allowing simple introduction to concepts commonly judged complex. Taking into account the early contact of children with technology (especially mobile phones and tablets), the platform consists of two main modules: a robot-car responsible for receiving commands like "move forward", "turn left" and "turn right", and an application for Android devices responsible for the graphic interface of the platform and for sending commands to the robot-car. The platform's goal is, besides teaching programming logic itself, to bring as soon as possible other probable latent benefits that may exist in its learning, always in a playful and engaging way for children. The platform was developed using a bottom-up approach, meaning that the elements were developed separately and then the connection was between them was created. In the conclusion, the viability of reproduction of the project is exposed, along with some future work proposals.